2016
DOI: 10.1037/dev0000183
|View full text |Cite
|
Sign up to set email alerts
|

Generics license 30-month-olds’ inferences about the atypical properties of novel kinds.

Abstract: We examined whether the distinction between generic and nongeneric language provides toddlers with a rapid and efficient means to learn about kinds. In Experiment 1, we examined 30-month-olds’ willingness to extend atypical properties to members of an unfamiliar category when the properties were introduced in one of three ways: a) using a generic noun phrase (“Blicks drink ketchup”); b) using a nongeneric noun phrase (“These blicks drink ketchup”); and c) using an attentional phrase (“Look at this”). Hearing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…First, generic language in scientific articles may lead readers to reach exaggerated conclusions. Past research found that generic sentences implied that a property was broadly true (28,35,45,46) and conceptually central (37,38), and that the category expressed was stable with inherent properties (41,47). In the present work, studies 2 to 4 similarly revealed that both online workers and undergraduates studying psychology judged research summaries with generic language to be more important than nongeneric summaries, and under certain circumstances to be more generalizable and conclusive.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…First, generic language in scientific articles may lead readers to reach exaggerated conclusions. Past research found that generic sentences implied that a property was broadly true (28,35,45,46) and conceptually central (37,38), and that the category expressed was stable with inherent properties (41,47). In the present work, studies 2 to 4 similarly revealed that both online workers and undergraduates studying psychology judged research summaries with generic language to be more important than nongeneric summaries, and under certain circumstances to be more generalizable and conclusive.…”
Section: Discussionsupporting
confidence: 53%
“…In studies 3a to 3d, we sought to replicate and extend the findings of study 2 by testing a broader range of linguistic cues to nongenericity. Language can signal nongenericity in a rich variety of ways, and most prior research has provided a starker contrast between generic and nongeneric than was provided in study 2 (28)(29)(30)(31)(32)(33)(34)(35). For example, whereas study 2 only manipulated tense, in the published literature, nongenerics typically manipulated the noun phrase itself (e.g., "This X. .…”
Section: Studies 3a To 3d: Multiple Cues To Nongenericitymentioning
confidence: 99%
“…Preschool children appreciate both these points (46,58). Moreover, hearing novel generics about novel categories leads to more within-category inferences (36,112), assumption of core features (57), and essentialist inferences about that category, above and beyond labeling per se (108,109).…”
Section: Two Presuppositions: Norms and Essencesmentioning
confidence: 99%
“…As soon as children master the syntactic prerequisites for expressing generics in their language (e.g., in English: plurals, articles, and tense), they produce generics ("Does lions crawl? "; "I don't like babies that cry"), comprehend generics as kind-referring and distinct from specific reference, and recall whether information was provided using generic or specific language (35)(36)(37). Generics have been attested in all documented languages, including pidgins and Pirahã (38-42).…”
Section: Categories As Cultural Inheritancementioning
confidence: 99%
“…For example, children as young as 2.5 years of age rely on taxonomic relations (e.g., birds) when projecting potentially shared properties (e.g., lives in a nest; Gelman and Coley, 1990). Indeed, even 14-16 month old infants' use of labels suggests sensitivity to the importance of membership in taxonomic categories to guide inferences (Keates and Graham, 2008; see also Ferry et al, 2010;Graham et al, 2016;Switzer and Graham, 2017). This and other work (for reviews, see Coley et al, 2002;Coley and Muratore, 2012) suggest that taxonomic relations based on intrinsic, inherent similarities can be more salient for young children than thematic relations.…”
Section: Beyond a 'Thematic To Taxonomic Shift'?mentioning
confidence: 99%